Unlocking the potential of green synthesis: biogenic silver nanoparticles enhance biomass and bioactive chemicals in Ricinus communis Callus - Abdel-Rhman Z. Gaafar; Ahmed A. Qahtan; Abdulrahman A. Alatar (Biotechnology & Biotechnological Equipment)
Harnessing the power of nature, this study delves into the remarkable influence of biosynthesized silver nanoparticles (AgNPs) on biomass production and bioactive chemical synthesis in Ricinus communis callus. Leveraging the eco-friendly properties of Calligonum comosum leaf aqueous extract as both reducing and capping agents, the synthesis of AgNPs was meticulously characterized through an array of analytical techniques, including FTIR, UV-vis spectroscopy, XRD, SEM, TEM, and EDS, confirming the triumphant creation of biogenic AgNPs. Unveiling a landscape of possibilities, the assessment of R. communis biomass and phytochemical substances unraveled intriguing insights. Results unveiled a resounding enhancement in biomass production upon the introduction of biosynthesized AgNPs to the plant media. Noteworthy is the revelation that increasing concentrations of silver NPs acted as catalysts for heightened plant growth and enriched physiological parameters. Moreover, the application of silver nitride elicited a profound amplification in both biomass and antioxidant enzyme activities within plant cells. However, amidst these triumphs, a curious observation emerged: the activities of superoxide dismutase (SOD), catalase (CAT), and ascorbate peroxidase (APX) exhibited a notable decline with escalating doses of AgNPs. In essence, this groundbreaking study not only underscores the potential of biosynthesized AgNPs to orchestrate a symphony of growth and biochemical synthesis within R. communis callus but also beckons forth an era of exploration. By charting a course for future research, it beckons scientists to delve deeper into the intricate pathways of phytochemical production and bioactive molecule synthesis under the influence of AgNPs.